Extraction of Flavonoid From Mangosteen Peel (Garcinia Mangostana) Using Ultrasound–Assisted (UAE) Extraction and Its SPF Value - Eduardus Budi Nursanto; Mohammad Afief Fisouti Pitoyo; Nur Layli Amanah; Andini Fikarda (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2026)
In this study, the peel of mangosteen (Garcinia mangostana) will be extracted to develop a natural sunscreen formulation. Mangosteen peel is rich in natural antioxidants, including flavonoids, tannins, triterpenoids, and phenolic compounds. The primary objectives are to determine the yield, Total Flavonoid Content (TFC), and to evaluate the Sun Protection Factor (SPF) of the ethanolic extract obtained from the mangosteen peel. Ultrasound-Assisted Extraction (UAE) will be employed, with a fixed extraction time of 45 minutes. Two consentrations of ethanol are used, 96% and 70%, respectively. The ratio of the material to the solvent used are 1:15, 1:25, and 1:35 gr/mL. This study reports the highest SPF value was obtained from the 70% ethanol extract, using a material-to-solvent ratio of 1:35 g/mL, which yielded 15.111% and exhibited an SPF of 16.009 (unitless). In contrast, the highest TFC was observed in the 96% ethanol extract, with a concentration of 2,549 mg quercetin equivalents (QE) per gram of extract.